Reduction of Nitrogen Oxides by Hydrogen with Rhodium(I)–Platinum(II) Olefin Complexes as Catalysts. (20th October 2021) - Jurt, Pascal; Abels, Anne Sofie; Gamboa‐Carballo, Juan José; Fernández, Israel; Le Corre, Grégoire; Aebli, Marcel; Baker, Matthew G.; Eiler, Frederik; Müller, Fabian; Wörle, Michael; Verel, René; Gauthier, Sébastien; et al.
Abstract: The nitrogen oxides NO2, NO, and N2 O are among the most potent air pollutants of the 21 st century. A bimetallic Rh I –Pt II complex containing an especially designed multidentate phosphine olefin ligand is capable of catalytically detoxifying these nitrogen oxides in the presence of hydrogen to form water and dinitrogen as benign products. The catalytic reactions were performed at room temperature and low pressures (3–4 bar for combined nitrogen oxides and hydrogen gases). A turnover number (TON) of 587 for the reduction of nitrous oxide (N2 O) to water and N2 was recorded, making these Rh I –Pt II complexes the best homogeneous catalysts for this reaction to date. Lower TONs were achieved in the conversion of nitric oxide (NO, TON=38) or nitrogen dioxide (NO2, TON of 8). These unprecedented homogeneously catalyzed hydrogenation reactions of NOx were investigated by a combination of multinuclear NMR techniques and DFT calculations, which provide insight into a possible reaction mechanism. The hydrogenation of NO2 proceeds stepwise, to first give NO and H2 O, followed by the generation of N2 O and H2 O, which is then further converted to N2 and H2 O. The nitrogen−nitrogen bond‐forming step takes place in the conversion from NO to N2 O and involves reductive dimerization of NO at a rhodium center to give a hyponitrite (N2 O2 2− ) complex, which was detected as an intermediate. Abstract : Catalyzed hydrogenation of NO2, NO, and N2 O is achieved under mild conditions by air stable olefin Rh I –Pt II bimetallic complexes. In the molecular catalysts, the Rh–Pt interaction is a direct metal−metal bond and cooperativity of both metals in substrate activation is proposed based on DFT. A hyponitrite rhodium complex is a key intermediate for the N−N bond‐forming step in the catalytic reduction of NO.